THE KINEMATICS PARAMETERS OF THE GALAXY USING DATA OF MODERN ASTROMETRIC CATALOGUES - Akhmetov, V. S.; Fedorov, P. N.; Velichko, A. B.; Shulga, V. M. (Одеські астрономічні публікації, 2016)
Based on the Ogorodnikov-Milne model, we analyze the proper motions of XPM2, UCAC4 and PPMXL stars. To estimate distances to the stars we used the method of statistical parallaxes herewith the random errors of the distance estimations do not exceed 10%. The method of statistical parallaxes was used to estimate the distances to stars with random errors no larger than 14%. The linear solar velocity relative to the local standard of rest, which is well determined for the local entroid (d 150 p), was used as a reference. We have established that the model component that describes the rotation of all stars under consideration about the Galactic Y axis differs from zero. For the distant (d < 1000 pc) PPMXL and UCAC4 stars, the mean rotation about the Galactic Y axis has been found to be M-13 = -0.75± 0.04 mas yr-1. As for distances greater than 1 kpc M-13derived from the data of only XPM2 catalogue becomes positive and exceeds 0.5 mas yr-1. We interpret this rotation found using the distant stars as a residual rotation of the ICRS/Tycho-2 system relative to the inertial reference frame.